Optimization of a jump shot rhythm at the junior level of basketball performance - Bazanov, B.; Rannama, I.; Sirel, K. (Journal of Human Sport & Exercise, 2015)
The jump shot is one of the most frequently used methods of shooting in the modern basketball. For example in the Spanish league, it accounts for 41% of all points (Rojas et al, 2000). Based on the results of our previous research which enabled to determine the phase structure and create rhythm models of shooting in elite male basketball (Bazanov, B. 2001, 2014) the purpose of this study was to improve the shooting rhythm of jump shot performances of male under 20 years old basketball players. The subjects used consisted of five under 20 years old basketball players of the Tallinn Basketball Academy. The whole action of shooting was divided into 5 phases and examined quantitatively and qualitatively. The data obtained were analyzed using descriptive statistics. The reliability of the differences was controlled by F-test and T-test. Results show, that the main changes occurred in preparation ("catching" and "sitting down") phases. We can conclude, that execution of technical requirements allows to change significantly the jump shot rhythm performance and reduce the duration of the jump shot in basketball.